DIAGNOSIS KESULITAN BELAJAR DAN PERBAIKAN BELAJAR (REMEDIAL) - Yunus, Sahriah (Transpublika Publisher, 2021)
Diagnosis is the endeavor or process of determining the nature of a person's weakness or disease via meticulous testing and examination of the symptoms. A thorough examination of the facts surrounding a subject in order to ascertain fundamental qualities or errors, and so on, in order to determine that the notion of diagnosis encompasses the concept of prognosis. Thus, diagnostic work entails not only determining the nature, characteristics, and context of a given weakness or sickness, but also attempting to forecast its potential and offering a solution. Before teachers can make improvements to students' learning, they must first diagnose learning issues, which includes defining the types and reasons of difficulties, as well as possible solutions. Efforts to improve learning include the following steps: (1) Prognosis for planning/programming activities likely to assist pupils in overcoming their learning challenges (2) Treatment is the planning/programming of activities aimed at assisting students with learning issues; treatment here refers to assisting the student in accordance with the program developed during the prognosis stage. (3) The purpose of this evaluation is to determine whether the treatment described above was effective, and/or whether there was progress or even failure.